Manajemen Pembiayaan Pendidikan Dalam Meningkatkan Mutu Pendidikan Madrasah - Fauzi, Alfan; Afifurrohman, Afifurrohman (STAI Denpasar Bali, 2024)
The purpose of the research is to provide light on how managing student loans can enhance madrasah quality. This study's methodology is based on a library methodology or strategy, that can be defined as a set of procedures for gathering information from libraries, reading and taking notes, and processing research materials. According to the results of the research, financing management is the act of making the most of already-existing funding sources, assigning available monies, and distributing them as resources or tools to aid in the learning process in order to establish a productive and successful learning environment. Cost management of education is essential to achieving the highest levels of madrasah quality. As a result, it is important to take into account the stages of education financing management. The effective use of funds for each madrasah should determine a plan that is a comprehensive educational financing priority from a financing program that entails crucial choices about the state funding allocation system for school regions or areas, the tax system utilized to finance the program, and the courses of study that must be paid.